Unveiling the reaction pathway on Cu/CeO2 catalyst for electrocatalytic CO2 reduction to CH4 - Xue, Lei; Zhang, Chunjuan; Wu, Jinfang; Fan, Qi-Yuan; Liu, Yang; Wu, Yanxin; Li, Jiaxin; Zhang, Heng; Liu, Fenrong; Zeng, Shanghong (Applied catalysis. B, Environmental, 2022)
The determination of reaction mechanism for electrocatalytic CO2 reduction by experiments is still out of reach on copper catalyst, which limits its advance towards industrial implementation. Here, the Cu/CeO2 catalyst as paradigm was studied to validate the reaction intermediates and pathway. The Cu/CeO2 catalysts with different morphologies were synthesized, and it is discovered that the nanorod Cu/CeO2 catalyst exhibits high selectivity for CO2-to-CH4 with the highest turnover frequency for CH4 production among the samples. Detailed study indicates that the nanorod Cu/CeO2 possesses the largest electrochemically active surface area, higher proportion of O-vacancy sites, and better capability of CO2 adsorption and activation. The chemical nature above together contributes to its high activity. Theoretical calculations reveal that the doping of Cu into CeO2 can significantly lower the reaction energy barrier of *CO2 →*COOH and change the reaction pathway from *CHOH →*CH2OH to *CHOH →*CH, effectively improving the catalytic performance for CO2 electroreduction. [Display omitted] •Cu/CeO2 catalyst as paradigm for validating reaction intermediates and pathway.•FE toward CH4 reaches 49.3% with a TOF of 8000 h−1 for nanorod Cu/CeO2 catalyst.•Cu doping into CeO2 can significantly lower reaction energy barrier of *CO2 →*COOH.•Cu doping also changes reaction pathway from *CHOH →*CH2OH to *CHOH →*CH in CO2RR.